Работа с семьей ребенка с ограниченными возможностями здоровья - Богданова, Т.В.; Симакович, Н.П. (My University, 2013)
Article is devoted to topical issue of correctional and pedagogical activity where work basics with a family of the child with limited opportunities of health are covered.